INFUSING ISLAMIC VALUES AND SUSTAINABLE DEVELOPMENT INTO CHEMISTRY FOR PRE-SERVICE ISLAMIC ELEMENTARY SCHOOL TEACHERS - Muhamad Imaduddin (Pendidikan Kimia Unimus, 2019)
This paper discusses the designs in infusing Islamic values and sustainable development and how challenges must be faced in the training for pre-service Islamic elementary school teachers. The subjects of this study consisted of 77 primary school educational candidates who contracted